The International Legal Frame-work for Protecting Children during Armed Conflicts: A Case Study of Israel-Palestine Conflict - Aisha Cheema; Dr. Iftikhar Ahmad; Dr. Ramzan Shahid (Corresponding Author) (`, 2025)
The Israel-Palestine conflict, characterized by prolonged violence and violations of international law, has had devastating humanitarian consequences, particularly for Palestinian children. This research article explores the systematic violations committed by Israel, including genocide, war crimes, and crimes against humanity, focusing on the impact on Palestinian civilians. It discusses the destruction of homes, infrastructure, and healthcare facilities, food and water insecurity, and the violation of children’s rights, as outlined by international treaties like the Fourth Geneva Convention and the Convention on the Rights of the Child. The article calls for immediate action from the United Nations and the International Court of Justice to investigate these violations and hold Israel accountable. Additionally, it recommends humanitarian interventions such as providing essential aid, rebuilding infrastructure, and ensuring the safety of Palestinian civilians, particularly children. While the focus is on the suffering of Palestinian people, the article also acknowledges the impact of the conflict on Israeli civilians. The ultimate goal is to foster a lasting peace that ensures the rights and dignity of all people involved. Keywords: Israel-Palestine Conflict, Human Rights Violations, Genocide, War Crimes, Children’s Rights, Humanitarian Intervention